The Role of Political Actors’ Preference Variation in the Decision-Making Process of the European Union - Yuxuan Lei (Social Sciences)
Member states and interest groups, as key political actors, play crucial roles in the decision-making process of the European Union (EU). This study examines the relationship between the variation in political actors’ preferences and decision-making procedures, emphasizing the roles of interest groups and member states as critical stakeholders. This research employs a process-tracing method, analyzing two case studies—the Transatlantic Trade and Investment Partnership (TTIP) and the EU Emissions Trading System (EU ETS)—to investigate the causal mechanisms linking preference heterogeneity to the duration of decision-making processes. The findings reveal that preference heterogeneity functions as a multidimensional factor, encompassing not only disagreements but also the interplay of diverse interest group demands and the strategic positioning of member states within institutional frameworks. By identifying the specific mechanisms of these interactions, this study underscores the importance of accounting for varying levels of issue salience and their impact on procedural dynamics when devising legislative strategies.